2008
DOI: 10.5194/bgd-5-1139-2008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The significance of organic carbon and nutrient export from peatland-dominated landscapes subject to disturbance

Abstract: Abstract. The terrestrial-aquatic interface is a crucial environment in which to consider the fate of exported terrestrial carbon in the aquatic system. To a large extent the fate of dissolved organic carbon (DOC) may be controlled by nutrient availability. However, peat-dominated headwater catchments are normally considered of low nutrient status and thus there is little data on the interaction of DOC and nutrients. Here we present nutrient and DOC data exported from two UK catchments, both dominated by peat … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…This is consistent with the findings of chemical and isotopic studies of peatland drainage waters (e.g. Waldron et al 2009), which have revealed that, although disturbed peatlands do release more dissolved and suspended organic carbon to downstream catchments than undisturbed ones, the scale of carbon loss is a lot more modest than was originally feared. However, as the site studied by Waldron et al (2009) had only recently been disturbed, that finding may not transfer to sites subject to longer periods of disturbance.…”
Section: Hydrogeological Contributions To Other Renewable Energy Techsupporting
confidence: 80%
See 2 more Smart Citations
“…This is consistent with the findings of chemical and isotopic studies of peatland drainage waters (e.g. Waldron et al 2009), which have revealed that, although disturbed peatlands do release more dissolved and suspended organic carbon to downstream catchments than undisturbed ones, the scale of carbon loss is a lot more modest than was originally feared. However, as the site studied by Waldron et al (2009) had only recently been disturbed, that finding may not transfer to sites subject to longer periods of disturbance.…”
Section: Hydrogeological Contributions To Other Renewable Energy Techsupporting
confidence: 80%
“…Waldron et al 2009), which have revealed that, although disturbed peatlands do release more dissolved and suspended organic carbon to downstream catchments than undisturbed ones, the scale of carbon loss is a lot more modest than was originally feared. However, as the site studied by Waldron et al (2009) had only recently been disturbed, that finding may not transfer to sites subject to longer periods of disturbance. Thus further research is needed, on a wider range of sites and over longer time scales, to determine whether such conclusions are indeed generally valid for upland peat ecosystems affected by wind turbine developments.…”
Section: Hydrogeological Contributions To Other Renewable Energy Techmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, DOC impacts water quality in terms of color, taste, safety, and aesthetic value, as well as altering the acid-base and metal complexation characteristics of soil water and stream water. Together with the C losses considerable nutrient export may occur as well, potentially increasing impacts on aquatic diversity downstream (Waldron et al, 2008). DOC accumulates in peat pore waters and is flushed out by water movement, with concentrations often greatest following periods of warm, dry conditions when DOC has had time to accumulate.…”
Section: Doc Fluxesmentioning
confidence: 99%
“…Many temperate peatlands have been drained for commercial exploitation such as agriculture, forestry or more recently windmill farming (Waldron et al, 2008). This has resulted in profound effects on peatland biogeochemistry, Gorham (1995), (B).…”
Section: Land Use Changesmentioning
confidence: 99%